The Learning Curve for Transradial Percutaneous Coronary Intervention among Operators in the United States: A Study from the National Cardiovascular Data Registry® - Hess, Connie N. (2014)
BACKGROUND: Adoption of TRI in the United States is low and may be related to challenges learning the technique. We examined the relationships between operator transradial percutaneous coronary intervention (TRI) volume and procedural metrics and outcomes. METHODS AND RESULTS: We used CathPCI Registry(®) data from 07/2009–12/2012 to identify new radial operators, defined by an exclusively femoral PCI approach for 6 months after their first PCI in the database and ≥15 total TRIs thereafter. Primary outcomes of fluoroscopy time, contrast volume, and procedure success were chosen as markers of technical proficiency. Secondary outcomes included in-hospital mortality, bleeding, and vascular complications. Adjusted outcomes were analyzed using operator TRI experience as a continuous variable with generalized linear mixed models. Among 54,561 TRI procedures performed at 704 sites, 942 operators performed 1–10 cases; 942 operators performed 11–50 cases; 375 operators performed 51–100 cases; and 148 operators performed 101–200 cases. As radial caseload increased, more TRIs were performed in women, in STEMI patients, and for emergency indications. Decreased fluoroscopy time and contrast use were non-linearly associated with greater operator TRI experience, with faster reductions observed for newer (<30–50 cases) compared with more experienced (>30–50 cases) operators. Procedure success was high, while mortality, bleeding, and vascular complications remained low across TRI volumes. CONCLUSIONS: As operator TRI volume increases, higher risk patients are chosen for TRI. Despite this, operator proficiency improves with greater TRI experience, and safety is maintained. The threshold to overcome the learning curve appears to be approximately 30–50 cases.